Intra-organizational knowledge sharing in the construction industry: A case study of knowledge sharing practices between supervisors in a major infrastructure project - Hernstig, Marcus; Zafar, Mona (My University, 2021)
For many years, several studies have been conducted about knowledge sharing (KS) in the construction sector, since it has been connected to a company’s ability to stay successful in a competitive market. Construction companies has been seeking to im prove their KS capabilities in order to increase operational efficiency and decrease construction costs. However, while there already exists great amounts of knowledge in the construction industry, the companies are unable take advantage of the shared knowledge. This master’s thesis has been made together with one of the largest construction company in Sweden, which was involved in a major infrastructure project. The aim of this master’s thesis has been to investigate if there exists any KS practices be tween Supervisors in the various Area and Trade Blocks, what barriers and enablers there might have been for establishing KS practices, and finally propositions were made what the contracting company could do to more easily facilitate KS activities between Supervisors. An empirical study was conducted where Supervisors, Area Site managers, Trade Site managers, Trade Block managers and an Environmental coordinator were interviewed within the project. The interviews were performed in a semi-structured manner where questions were prepared beforehand. In addition, a literature review was carried out throughout the project which has provided relevant information about KS. This report has provided insight into KS practices at a lower managerial level in a complex infrastructure project. Further, this master’s thesis has suggested that KS practices is not prioritized in the construction sector, and neither in relation to this report. It was indicated that there is a lack of systematized way of sharing knowledge between Supervisors in the various blocks. The Supervisors mostly gain operational knowledge through verbal communication, over informal channels such as through meetings and personal interactions. Furthermore, the contracting com pany is lacking infrastructure within the organization which could capture shared knowledge between the Supervisors. Other barriers for KS between Supervisors are connected to a lack of time, a project-based environment, and an unclear responsi bility area for enabling KS activities within the project. However, the employees have a will to support as well as improve KS between Supervisor. Therefore, the case company have great potential to improve accessibil ity of KS between Supervisors through monthly meetings, workshops, digital weekly letters, electronic list of contact details, video conferences, job rotations and through physical site visits to a certain Area or Trade Block. The goal should be to create a learning environment within the organization in which the Supervisors can avoid repeat operational mistakes.
Keywords: Knowledge; Knowledge Sharing; Data; Information; Barriers and Enablers for Knowledge Sharing in the Construction industry; Communities of Practice; Communities of Practice in the Construction Industry; ICT; Information and communication technology in the construction industry